A Study on the Outcome of Targeted Temperature Management Comparing Cardiac Arrest Patients Who Received Bystander Cardiopulmonary Resuscitation With Those Who Did Not, Using the Nationwide TIMECARD Multicenter Registry - Liou, Fang-Yu; Tsai, Min-Shan; Kuo, Li-Kuo; Hsu, Hsin-Hui; Lai, Chih-Hung; Lin, Kun-Chang; Huang, Wei-Chun (Frontiers in Medicine, 2022)
Background and Purpose Targeted temperature management (TTM) is associated with decreased mortality and improved neurological function after cardiac arrest. Additionally, studies have shown that bystander cardiopulmonary resuscitation (BCPR) doubled the survival of patients with out-of-hospital cardiac arrest (OHCA) compared to patients who received no BPCR (no-BCPR). However, the outcome benefits of BCPR on patients who received TTM are not fully understood. Therefore, this study aimed to investigate the outcome differences between BCPR and no-BCPR in patients who received TTM after cardiac arrest. Methods The Taiwan Network of Targeted Temperature Management for Cardiac Arrest (TIMECARD) multicenter registry established a study cohort and a database for patients receiving TTM between January 2013 and September 2019. A total of 580 patients were enrolled and divided into 376 and 204 patients in the BCPR and no-BCPR groups, respectively. Results Compared to the no-BCPR group, the BCPR group had a better hospital discharge and survival rate (42.25 vs. 31.86%, P = 0.0305). The BCPR group also had a better neurological outcome at hospital discharge. It had a higher average GCS score (11.3 vs. 8.31, P < 0.0001) and a lower average Glasgow–Pittsburgh cerebral performance category (CPC) scale score (2.14 vs. 2.98, P < 0.0001). After undertaking a multiple logistic regression analysis, it was found that BCPR was a significant positive predictor for in-hospital survival (OR = 0.66, 95% CI: 0.45–0.97, P = 0.0363). Conclusions This study demonstrated that BCPR had a positive survival and neurological impact on the return of spontaneous circulation (ROSC) in patients receiving TTM after cardiac arrest.